2020
DOI: 10.1021/acscatal.0c03762
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of Boron-Based Oxidative Dehydrogenation Heterogeneous Catalysts With Ultrahigh Field 35.2 T 11B Solid-State NMR Spectroscopy

Abstract: Boron-based heterogeneous catalysts, such as hexagonal boron nitride (h-BN) as well as supported boron oxides, are highly selective catalysts for the oxidative dehydrogenation (ODH) of light alkanes to olefins. Previous catalytic measurements and molecular characterization of boron-based catalysts by 11 B solid-state NMR spectroscopy and other techniques suggest that oxidized/ hydrolyzed boron clusters are the catalytically active sites for ODH. However, 11 B solid-state NMR spectroscopy often suffers from lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 83 publications
8
62
0
Order By: Relevance
“…Alternatively, an MCM‐22 zeolite isomorphously substituted with boron primarily contains B (OSi) 3 species isolated in the zeolite framework and is inactive for ODH. This observation further supports the hypothesis that the clustering of oxidized/hydrolyzed boron gives rise to its ODH catalytic activity [12,14] . However, B/SiO 2 catalysts show worse selectivity for ODH of propane to propylene than h‐BN (B/SiO 2 : 76.5 %, h‐BN: 87.4 %; Figure 2b), which is attributed to oxygen functionalities on the silica surface that induce unwanted side reactions with intermediates [5] .…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…Alternatively, an MCM‐22 zeolite isomorphously substituted with boron primarily contains B (OSi) 3 species isolated in the zeolite framework and is inactive for ODH. This observation further supports the hypothesis that the clustering of oxidized/hydrolyzed boron gives rise to its ODH catalytic activity [12,14] . However, B/SiO 2 catalysts show worse selectivity for ODH of propane to propylene than h‐BN (B/SiO 2 : 76.5 %, h‐BN: 87.4 %; Figure 2b), which is attributed to oxygen functionalities on the silica surface that induce unwanted side reactions with intermediates [5] .…”
Section: Introductionsupporting
confidence: 80%
“…The enhanced performance of h‐BN for ODH is attributed to an amorphous oxidized/hydrolyzed boron layer [B 2 (OH) 2x O 3‐x , x=0–3] which resides on the BN sheets [2,7–10] . Solid‐state NMR spectroscopy and other surface characterization techniques have shown that the amorphous oxidized/hydrolyzed boron layer is primarily composed of 3‐coordinate boron oxide/hydroxide species (B 2 (OH) 2x O 3‐x , x=0–3) that form under reaction conditions [2,9,11,12] . Ultra‐high field 11 B NMR spectroscopy revealed that the oxidized/hydrolyzed boron layer grows off the BN sheets through B N 2 O groups, where the O atom is bridging to the oxidized/hydrolyzed boron layer [12] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both NMR active Mo nuclei 95 Mo and 97 Mo are quadrupolar nuclei of spin 5/2. Due to the low gyromagnetic ratio nature, γ( 95 Mo)=−1.751×10 7 rad T −1 s −1 and γ( 97 Mo)=−1.78×10 7 rad T −1 s −1 , sensitivity‐enhanced WURST‐QCPMG method was employed in combination with ultra‐high magnetic field of 35.2 T (1.5 GHz) which shows advantages for high‐resolution NMR spectroscopy of half‐integer quadrupolar nuclei [44–48] . The 95 Mo WURST‐QCPMG MAS NMR spectrum acquired at 35.2 T of the fresh 5Mo/ZSM‐5 exhibits a broad quadrupolar peak ( C Q ≈5.5 MHz) with an isotropic chemical shift (δ iso ) of ca.…”
Section: Resultsmentioning
confidence: 99%